Music, Imagination & Culture - Cook, Nicholas (Oxford Clarendon, 1992)
It is a common experience that words are inadequate for music; there seems always to be a disparity between how music is experienced, and how it is described or rationalized. This book is a study of musical imagination. Musicians imagine music by means of functional models which determine certain aspects of the music while leaving others open. This means that there is inevitably a gap between the image and the experience that it models, and this gap can be a source of compositional creativity. Different musical cultures embody different ways of imagining sound as music, and thus every culture creates its own distinctive pattern of discrepancies between image and experience - discrepancies which are reflected in theoretical thinking about music. Drawing on psychological and philosophical materials as well as the analysis of specific musical examples, Nicholas Cook makes a clear distinction between the province of music theory and that of aesthetic criticism. In doing so he affirms the importance of the `ordinary listener' in musical culture, and the validity of his or her experience of music.